Using fisheries by‐catch data to predict octocoral habitat suitability around South Georgia - Michelle L. Taylor; Chris Yesson; David J. Agnew; Rebecca E. Mitchell; Alex D. Rogers (Journal of Biogeography, 2013)
Aim For many deep‐sea fisheries, there is an urgent management requirement for information on the presence of vulnerable marine ecosystems ( VME s). Gathering deep‐sea data using conventional techniques can be expensive and time‐consuming. One way to provide a relatively rapid assessment of VME presence is to use data from fisheries by‐catch and historical scientific observations. Our aim was to predict suitable habitat for octocorals around South Georgia and to estimate the extent to which octocoral habitat is currently protected by fisheries management measures. In addition, we attempted to determine the types of terrain in which octocorals and fishing activities occur. Location South Georgia, sub‐Antarctic. Methods A terrain map of South Georgia was created using Benthic Terrain Modeler ( BTM ). Georeferenced octocoral data were combined with environmental layers to create an octocoral habitat suitability map using ecological niche factor analysis ( ENFA ). Results Most octocoral by‐catch samples originated from narrow crest (an area representing shelf break and moraines) and steep (continental) slope terrains. Calcite saturation state and apparent oxygen utilization ( AOU ) were the most influential environmental parameters in determining highly suitable octocoral habitat. The ENFA model highlighted shelf‐break areas to be highly suitable habitat for octocorals and that 38% of this habitat around South Georgia lies within areas currently protected by fisheries management; a further 20% is below the 2000‐m fishing depth, meaning effectively that 58% of predicted highly suitable octocoral habitat is currently protected. Although these results indicate protection levels for octocoral habitat well above international standards/targets, the fishery remains active within a relatively concentrated shelf area at 700–2000 m, potentially having a large impact on the 42% of highly suitable octocoral habitat predicted to lie at these depths. Main conclusions This research demonstrates the potential for using fisheries by‐catch data to create habitat suitability maps that can inform fisheries management and future research.